Persepsi keamanan, persepsi privasi, pengalaman serta kepercayaan terhadap belanja online - Arman Efendi; Rahmiati Rahmiati (Jurnal Kajian Manajemen Bisnis, 2020)
This study aims to analyze: (1) The effect of security perception on trust in online shopping (2) The effect of privacy perception on trust in online shopping (3) The effect of online shopping experience on trust in online shopping. The type of research is descriptive causative. The population in this study is all Padang city communities who have made purchases through online stores. In this study the number of samples is determined using the Slovin formula with the acquisition of a total sample of 150 people taken using non-probability sampling. This research was conducted by multiple regression analysis. Regarding the proposed causal model, the data confirms the relationship established in the hypothesis. Therefore, it can be stated that (1) Security perception has a significant positive effect on online shopping trust (2) Privacy Perception has a significant positive effect on online shopping trust (3) online shopping experience has a significant positive effect on online shopping trust. This analysis highlights the positive influence of security perceptions, privacy perceptions and online shopping experiences on online shopping trust. This is clearly seen in this relationship from an empirical point of view. Keywords: Trust; security perception; privacy perception; online shopping; experience.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//